The Prospect of Global Coral Reef Bathymetry by Combining Ice, Cloud, and Land Elevation Satellite-2 Altimetry With Multispectral Satellite Imagery - Gleason, Arthur C. R.; Smith, Ross; Purkis, Sam J.; Goodrich, Kyle; Dempsey, Alexandra; Mantero, Alejandro (Frontiers in Marine Science, 2021)
Empirical methods for estimating shallow-water bathymetry using passive multispectral satellite imagery are robust and globally applicable, in theory, but they require copious local measurements of water depth for algorithm calibration. Such calibration data have historically been unavailable for most locations, but NASA’s Ice, Cloud, and Land Elevation Satellite-2 (ICESat-2), a satellite-based LiDAR, might hold unique promise to fill this critical data gap. Although ICESat-2 was not designed as a marine altimeter, its ATLAS sensor consists of six green (532 nm) lasers that can penetrate a water surface and return photons reflected by the seabed, thereby generating bathymetric profiles. Utilizing TCarta’s NSF SBIR-funded Space-Based Laser Bathymetry Extraction Tool and ICESat-2’s ATL03 geolocated photon data product, we have compared ICESat-2 bathymetric retrievals with a portfolio of soundings acquired in situ using a vessel-mounted single-beam echosounder. This analysis demonstrated very high correlation (R2 = 0.96) between the field and space-based bathymetry data. The comparisons were made at multiple Caribbean and Pacific coral reef sites over water depths ranging from 1 to 20 m. Results suggest that ICESat-2 could be an effective approach for calibrating and validating empirical and radiative transfer methods, alike, for estimating shallow-water bathymetry from remote sensing imagery, thereby enabling the immediate potential for shallow-water bathymetric mapping of Earth’s reefs.